COVID-19 pandemic : lessons from Lee Kuan Yew - Kwang, Han Fook (2020)
Singapore’s founding Prime Minister Lee Kuan Yew faced many crises in his lifetime, regional and global. Were he alive, he would have a lot to say about the present COVID-19 pandemic and how to deal with it. What lessons can Singapore and the rest of the world learn from his experience?